EFEKTIVITAS P’ZALM CARE WOUND CLEANSER SPRAY TERHADAP PENURUNAN POPULASI BAKTERI GRAM POSITIF DAN NEGATIF - Julianto, Eko; Suandika, Made (POLITEKNIK KESEHATAN KARYA HUSDA YOGYAKARTA, 2025)
ABSTRACT Background: Guava (Psidium guajava Linn) is a medicinal plant that is easy to find and can be grown in almost all areas. The content of active compounds in guava leaves, among others, are flavonoids and tannins that can reduce the incidence of infection in both acute and chronic wounds. Objective: This study aims to determine the effectiveness of P'Zalm Care Wound Cleanser Spray on decreasing the population of Gram Positive and Negative Bacteria. Methods: This study uses an experimental method with a pre-post test design approach with control. The sample was divided into an intervention group and a control group. The intervention group received P'zalm Care Wound Cleanser Spray without dilution and the control group, namely P'zalm Care Wound Cleanser Spray at a dilution of 1: 10, with an evaluation looking at the initial bacterial population and 30 seconds after being given the intervention then comparing the 3 types of Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli. Data collection is carried out after passing the ethical test. Results: The results showed that there was a significant effect of giving P'zalm Care Wound Cleanser Spray in the experimental group and the control group on gram-positive and gram-negative bacteria with a decrease in bacterial colonies of Log 6 log redox 99.9%. Conclusion: This research is guava leaf infusion has an antibacterial effect against Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli in Vitro with an effective concentration close to 100%. The increasing concentration of guava leaf infusion showed the larger the diameter of the growth inhibition zone of Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli. Keywords: P'zalm Care Wound Cleanser Spray, Psidium guajava Linn, gram negative bacteria